TO DEVELOP ARP-HPLC ASSAY METHOD FOR SIMULTANEOUS ESTIMATION OF ESCITALOPRAM&CLONAZEPAM FORIT’S QUANTIFICATION IN FINISHED DOSAGE FORM - Mehta, Deven; Chhabra, G. S.; Pednekar, Sanjay (Asian Journal of Pharmaceutical Research and Development, 2014)
A Simple, efficient and reproducible reverse phase high performance liquid chromatographic method was developed and validated for the Simultaneous determination of Escitalopram oxalate and Clonazepam in combined dosage form.The process was carried out on aInertsil C18 ODS 3V, 15 cm X 4.6 mm, 5µm or equivalent column. The flow rate was 1ml/min and eluent was monitored by absorbance at 254 nm using a mixture of Methanol and Buffer (pH 7.0) in the ratio of 55:45 (v/v). The retention times of Escitalopram and Clonazepam was found to be 17.3 and 10.02 min respectively. Calibration plots were linear in the concentration range of 80-120ppm and 8-12ppm for Escitalopram and clonazepam respectively. All the analytical validation parameters were determined and foundto be within the limit as per ICH guidelines, which indicates the validity of the method. The developed method is also found to be precise, accurate, specific, robust and rapid for the simultaneous determination of Escitalopram oxalate and Clonazepam in tablet dosage forms.